Space, Self and Place in the Novels of Sinclair Ross - Borkovich, Lisa (My University, 1988)
This study is an examination of the concepts of space, place and self, as I have applied them, in the works of Sinclair Ross. Having defined the meaning of these concepts in the Introduction, I show in Chapter One why space becomes a void waiting to engulf the lives of Ross's characters. I also suggest that a dichotomy exists within the context of these concepts between the world of the male and the world of the female that affects the way Ross's characters respond to space. In Chapter Two, I argue that Ross does not allow his female characters to establish a sense of self and place that would enable them to deal with the surrounding space (with specific reference to Mrs. Bentley in As For Me and My House). In Chapter Three, I explain how the men in Ross's work succeed, or, in the case of Philip Bentley in As For Me and My House, do not succeed, to structure and shape the physical space surrounding them by means of their identity and sense of place in life. For the purpose of facilitating my documentation of Ross's novels and the short stories, I shall use the following parenthetical abbreviations to denote the titles of the works, once they have been cited in the text of the thesis: As For Me and My House (AMMH), The Well (TW), Whir of Gold (WaG), Sawbones Memorial (SM), The Lamp at Noon and Other Stories (LN), and The Race and Other Stories by Sinclair Ross (TR).
Keywords: English Language and Literature; English Language and Literature